Quantifiable impact: monitoring landscape restoration from space. A regreening case study in Tanzania - van der Vliet, Mendy; Malbeteau, Yoann; Ghent, Darren; Haas, Sander de; Veal, Karen L.; van der Zaan, Thijs; Sinha, Rajiv; Dash, Saroj K.; Houborg, Rasmus; de Jeu, Richard A. M. (Frontiers in Environmental Science, 2024)
The impact of ecosystem conservation and restoration activities Ecosystem conservation and restoration activities are critical to reduce the vulnerability of biodiversity to climate change. Although these activities need to be evaluated objectively and systematically for effectiveness, they are rarely monitored from a global, multidimensional and multivariable perspective. Here we present an approach to quantify the environmental impact of landscape restoration using long-term and highresolution satellite observations. For two restoration areas in Tanzania, we can likely attribute an increase in the amount of water retained by the soil (~0.01 m³ m ³, ~13% average increase), a soil ⁻ temperature drop (~-0.5 °C) and an increase in surface greenness (~50% average increase) in 3.5 years. These datasets illuminate the impact of restoration initiatives on the landscape and support the reporting of comprehensive metrics to donors and partners. Satellite observations from commercial providers and space agencies are now achieving the frequency, resolution, and accuracy that can allow for the effective evaluation of restoration activities.